Existence of Traveling Fronts in a Food-Limited Population Model with Spatiotemporal Delay - Hai-Qin Zhao; San-Yang Liu (Journal of Applied Mathematics)
This paper is concerned with the traveling fronts of a diffusive food-limited population model with spatiotemporal delay. Sufficient conditions are established for the existence of traveling wave fronts by choosing different kinds of delay kernels. The approach used here is the upper-lower solution method and monotone iteration technique. Our work extends and/or covers some previous results.